Comparison of alumina ball size distribution in two white cement grinding units using Swebrec function (2019)
The results of characterizing the alumina ball size distribution in two mills of a crushing and grinding plant are shown. Themills were unloaded and the ball charge was screened in order to establish the ball size distribution. For both mills, the balls retained during the unloading were compared to the balls retained at the beginning of the process, and additionally, they were compared to the results obtained by the Swebrec adjusted distribution model. In both cases, the experimental data have had a good fit with this model. This practice is important in order to establish the best ball charge at the beginning of the operation and the ball recharge in the steady state.